(untitled) (Herald of the National Children’s Medical Center, 2024)
The aim of the study is to improve the results of diagnosis and treatment of various forms of cystic transformations of choledochus (CTX) in children, through the use of highly informative diagnostic methods and the introduction of new treatment technologies.